THE EFFECTS OF BANKRUPTCY AND REORGANISATION PLAN ON THE ECONOMIC SYSTEM OF SERBIA - Aničić, Dušan; Simić, Nataša; Petrović, Vesna (Journal of process management and new technologies, 2018)
Bankruptcy proceedings have wide-range implications for the economic system of the country, from unemployment, competitiveness, the reform process, etc; in a word, it has broad social effects. Therefore, the law should provide effective, simple and flexible management of the bankruptcy proceedings, with precisely established deadlines and clear consequences of the actions taken. The role of the state in bankruptcy proceedings is to preserve general social interest, stability and safety of the legal and economic systems. Reorganisation of the enterprises should lead to financial recovery of the debtor with the aim of its continuing to do business, settle debts (completely or partially) and become solvent and profitable afterwards. The success of reorganisation depends, among other things, on adequate financial analysis of the debtor. Due to a large number of companies (and considerable assets) in the process of bankruptcy and reorganisation, these processes are very important for the development of the economic system in Serbia.